2022
DOI: 10.3390/molecules27196314
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrooxidative Selenylation/Cyclization of Alkynes: Access to Functionalized Benzo[b]furans

Abstract: A mild, practical, metal and oxidant-free methodology for the synthesis of various C-3 selenylated benzo[b]furan derivatives was developed through the intramolecular cyclization of alkynes promoted with diselenides via electrooxidation. A wide range of selenium-substituted benzo[b]furan derivatives were obtained in good to excellent yields with high regioselectivity under constant current in an undivided cell equipped with carbon and platinum plates as the anode and cathode, respectively. Moreover, the converg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…In 2022, Ruan et al reported a catalyst and metal-free synthesis of selenylbenzo[ b ]furans using 2-alkynylanisole and diselenide under electrochemical conditions (Scheme 38). 92 The reaction was conducted at a constant current of 10 mA using n Bu 4 NBF 4 as the electrolyte in an undivided cell, in which graphite acted as the anode and a platinum plate acted as the cathode in the co-solvent of CH 3 CN and HFIP. The optimized reaction conditions were then applied to different 2-alkynylanisoles bearing various substituents.…”
Section: Intramolecular Selenofunctionalizationmentioning
confidence: 99%
“…In 2022, Ruan et al reported a catalyst and metal-free synthesis of selenylbenzo[ b ]furans using 2-alkynylanisole and diselenide under electrochemical conditions (Scheme 38). 92 The reaction was conducted at a constant current of 10 mA using n Bu 4 NBF 4 as the electrolyte in an undivided cell, in which graphite acted as the anode and a platinum plate acted as the cathode in the co-solvent of CH 3 CN and HFIP. The optimized reaction conditions were then applied to different 2-alkynylanisoles bearing various substituents.…”
Section: Intramolecular Selenofunctionalizationmentioning
confidence: 99%
“…A series of electrochemical methods, including the direct electrooxidative selenylation/cyclization of alkynes [112] and the versatile electrochemical synthesis of selenylbenzo[b]furan derivatives [113], were developed.…”
Section: + (Arsementioning
confidence: 99%
“…An efficient electrochemical protocol for the formation of valuable organylselenylated benzo[b]furan derivatives via the cyclization of 2-alkynylanisoles through an electrooxidative process was developed. Various 3-substituted benzofurans were obtained in good to excellent yields under metal-and oxidant-free mild reaction conditions (Scheme 28) [112]. This approach exhibited good functional group tolerance and could be easily scaled up with good efficiency, providing access to a diverse range of selenylated benzo[b]furans derivatives from available starting materials [112].…”
Section: + (Arsementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the electrochemical synthesis strategy has emerged as a powerful tool in organic synthesis due to its convenience, environmental sustainability, and controllability. [12] We were inspired by recent achievements in electrochemical transformations on selenylations, [13] and our continuous interest in electrochemical synthesis. [14] Herein, we developed a metal and oxidant-free electrochemical selenylation protocol for the synthesis of 3-selenylindoles from simple 2-alkynylanilines (Figure 2c).…”
mentioning
confidence: 99%